2019
DOI: 10.3389/fmicb.2019.02556
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Pandoraea, a Genus Enriched in Xenobiotic Biodegradation and Metabolism

Abstract: Comparative analysis of partial gyrB, recA, and gltB gene sequences of 84 Pandoraea reference strains and field isolates revealed several clusters that included no taxonomic reference strains. The gyrB, recA, and gltB phylogenetic trees were used to select 27 strains for whole-genome sequence analysis and for a comparative genomics study that also included 41 publicly available Pandoraea genome sequences. The phylogenomic analyses included a Genome BLAST Distance Phylogeny approach to calculate pairwise digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Paired-end 150 bp libraries were sequenced on an Illumina HiSeq4000 sequencer (Oxford Genomics Centre – Wellcome Centre for Human Genetics, Oxford, United Kingdom). Quality control, assembly and annotation were performed as described previously ( Peeters et al, 2019 ). Annotation was performed using Prokka v1.12 ( Seemann, 2014 ) with a genus-specific database based on reference genomes from the Burkholderia Genome Database v8.1 ( Winsor et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Paired-end 150 bp libraries were sequenced on an Illumina HiSeq4000 sequencer (Oxford Genomics Centre – Wellcome Centre for Human Genetics, Oxford, United Kingdom). Quality control, assembly and annotation were performed as described previously ( Peeters et al, 2019 ). Annotation was performed using Prokka v1.12 ( Seemann, 2014 ) with a genus-specific database based on reference genomes from the Burkholderia Genome Database v8.1 ( Winsor et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…As numerous studies have reported that this genus is dominant in the degradation of xenobiotics in bio lter systems (Portune et al, 2015, Allievi et al, 2018, this indicated a shift in degrading contribution away from Rhodococcus and more toward ASVs from the genera Devosia, Aquamicrobium, and Rhizobiales, which had high positive correlation with performance. The genus Pandoreae was reported to be highly enriched in species capable of effective degradation of xenobiotics (Peeters et al, 2019), and was positively correlated with r>0.7 in both bio lters as shown in Fig. 6.…”
Section: Discussionmentioning
confidence: 90%
“…As numerous studies have reported that this genus is dominant in the degradation of xenobiotics in biofilter systems [ 41 , 46 ], this indicated a shift in degrading contribution away from Rhodococcus and more toward ASVs from the genera Devosia , Aquamicrobium , and Rhizobiales , which had high positive correlation with performance. The genus Pandoraea was reported to be highly enriched in species capable of effective degradation of xenobiotics [ 47 ] and was positively correlated with r > 0.7 in both biofilters as shown in Fig. 6.…”
Section: Discussionmentioning
confidence: 99%